Recent advances and prospects in Prunus virology. (30th June 2017) - Rubio, M.; Martínez‐Gómez, P.; Marais, A.; Sánchez‐Navarro, J.A.; Pallás, V.; Candresse, T.
Abstract: The stone fruit genus Prunus, within the family Rosaceae, comprises more than 230 species, some of which have great importance or value as ornamental or fruit crops. Prunus are affected by numerous viruses and viroids linked to the vegetative propagation practices in many of the cultivated species. To date, 44 viruses and three viroids have been described in the 9 main cultivated Prunus species. Seven of these viruses and one viroid have been identified in Prunus hosts within the last 5 years. This work addresses recent advances and prospects in the study of viruses and viroids affecting Prunus species, mostly concerning the detection and characterisation of the agents involved, pathogenesis analysis and the search for new control tools. New sequencing technologies are quickly reshaping the way we can identify and characterise new plant viruses and isolates. Specific efforts aimed at virus identification or data mining of high‐throughput sequencing data generated for plant genomics‐oriented purposes can efficiently reveal the presence of known or novel viruses. These technologies have also been used to gain a deeper knowledge of the pathogenesis mechanisms at the gene and miRNA expression level that underlie the interactions between Prunus spp. and their main viruses and viroids. New biotechnological control tools include the transfer of resistance by grafting, the use of new sources of resistance and the development of gene silencing strategies using genetic transformation. In addition, the application of next generation sequencing and genome editing techniques will contribute to improving our knowledge of virus–host interactions and the mechanisms of resistance. This should be of great interest in the search to obtain new Prunus cultivars capable of dealing both with known viruses and viroids and with those that are yet to be discovered in the uncertain scenario of climate change.